The dream - Hunt, Roderick (Oxford Oxford university press, 2011)
Biff falls asleep and dreams of a scary dragon. Later she dreams of a gentle dolphin instead, which calms her fears and helps her sleep peacefully.
Biff visits the world of her dreams$1 (Bfirst encountering a dragon, then a dolphin$1 (Bbefore waking calmer and reassured.s
Keywords: English